Clinical Supervision and Principal Leadership's Influence on Teacher Performance - Mardiah, Leni; Ahyani, Nur; Mahasir, Mahasir (Yayasan Sembilan Pemuda Indonesia, 2022)
The purpose of this study is to evaluate and analyze: (1) the impact of clinical supervision on teacher performance; (2) the impact of principal leadership on teacher performance; and (3) the impact of clinical supervision and principal leadership combined on teacher performance. This is a quantitative study utilizing an ex post facto technique. This study was carried out at SMA Sub Rayon 18 Palembang, with a population of 265 teachers, and 159 persons were chosen at random as samples. Questionnaires are used to collect data. The validity test employs construction and content validity, and the reliability test use Cronbach's Alpha. The normality, linearity, multicollinearity, and hesteroscedasticity tests were used to examine the test criteria, and the data were analyzed using multiple linear regression approaches. The findings revealed that clinical supervision and principal leadership had a good and substantial influence on teacher performance.